Briten in Westfalen. Besatzer, Verbündete, Freunde?

Young People’s Travel Behavior – Using the Life-Oriented Approach to Understand the Acceptance of Autonomous Driving - Herrenkind, B.; Nastjuk, I.; Brendel, A.B.; Trang, S.; Kolbe, L.M. (Transportation Research Part D: Transport and Environment)

A meta-analysis of deterrence theory in information security policy compliance research - Trang, S.; Brendel, A. (Information Systems Frontiers)

Quaternary quadratic lattices over number fields - Kirschmer, Markus; Nebe, Gabriele (International Journal of Number Theory)
We relate proper isometry classes of maximal lattices in a totally definite quaternary quadratic space (V,q) with trivial discriminant to certain equivalence classes of ideals in the quaternion algebra representing the Clifford invariant of (V,q). This yields a good algorithm to enumerate a system of representatives of proper isometry classes of lattices in genera of maximal lattices in (V,q).
Keywords: Algebra and Number Theory

Automorphisms of even unimodular lattices over number fields - Kirschmer, Markus (Journal of Number Theory)
We describe the powers of irreducible polynomials occurring as characteristic polynomials of automorphisms of even unimodular lattices over number fields. This generalizes results of Gross & McMullen and Bayer-Fluckiger & Taelman.
Keywords: Algebra and Number Theory

Tempolimits und Grenzwerte: für eine evidenzbasierte verkehrspolitische Debatte - Habla, Wolfgang; Huwe, Vera; Kesternich, Martin
Keywords: Business; Management and Accounting (miscellaneous)

Eine City-Maut ist Diesel-Fahrverboten in Städten klar überlegen - Kesternich, Martin

Ethik zwischen Universalisierbarkeit und Lebensnähe. Zeitimplikate in den Referenzbegriffen der Ethikdefinition - Meyer zu Hörste-Bührer, Raphaela (Evangelische Theologie 79)

Editorial: Ethik in Antike und Christentum / Editorial: Ethics in Antiquity and Christianity - Meyer zu Hörste-Bührer, Raphaela (Journal of Ethics in Antiquity and Christianity 1)

Bi-Objective Orienteering: Towards a Dynamic Multi-objective Evolutionary Algorithm - Bossek, Jakob; Grimme, Christian; Meisel, Stephan; Rudolph, Günter; Trautmann, Heike (Evolutionary Multi-Criterion Optimization (EMO))
We tackle a bi-objective dynamic orienteering problem where customer requests arise as time passes by. The goal is to minimize the tour length traveled by a single delivery vehicle while simultaneously keeping the number of dismissed dynamic customers to a minimum. We propose a dynamic Evolutionary Multi-Objective Algorithm which is grounded on insights gained from a previous series of work on an a-posteriori version of the problem, where all request times are known in advance. In our experiments, we simulate different decision maker strategies and evaluate the development of the Pareto-front approximations on exemplary problem instances. It turns out, that despite severely reduced computational budget and no oracle-knowledge of request times the dynamic EMOA is capable of producing approximations which partially dominate the results of the a-posteriori EMOA and dynamic integer linear programming strategies.
Keywords: Combinatorial optimization; Dynamic optimization; Metaheuristics; Multi-objective optimization; Vehicle routing

Evolving Diverse TSP Instances by Means of Novel and Creative Mutation Operators - Bossek, Jakob; Kerschke, Pascal; Neumann, Aneta; Wagner, Markus; Neumann, Frank; Trautmann, Heike (Proceedings of the 15th ACM/SIGEVO Conference on Foundations of Genetic Algorithms)
Evolutionary algorithms have successfully been applied to evolve problem instances that exhibit a significant difference in performance for a given algorithm or a pair of algorithms inter alia for the Traveling Salesperson Problem (TSP). Creating a large variety of instances is crucial for successful applications in the blooming field of algorithm selection. In this paper, we introduce new and creative mutation operators for evolving instances of the TSP. We show that adopting those operators in an evolutionary algorithm allows for the generation of benchmark sets with highly desirable properties: (1) novelty by clear visual distinction to established benchmark sets in the field, (2) visual and quantitative diversity in the space of TSP problem characteristics, and (3) significant performance differences with respect to the restart versions of heuristic state-of-the-art TSP solvers EAX and LKH. The important aspect of diversity is addressed and achieved solely by the proposed mutation operators and not enforced by explicit diversity preservation.
Keywords: benchmarking; instance features; optimization; problem generation; traveling salesperson problem

Runtime Analysis of Randomized Search Heuristics for Dynamic Graph Coloring - Bossek, Jakob; Neumann, Frank; Peng, Pan; Sudholt, Dirk (Proceedings of the Genetic and Evolutionary Computation Conference)
We contribute to the theoretical understanding of randomized search heuristics for dynamic problems. We consider the classical graph coloring problem and investigate the dynamic setting where edges are added to the current graph. We then analyze the expected time for randomized search heuristics to recompute high quality solutions. This includes the (1+1) EA and RLS in a setting where the number of colors is bounded and we are minimizing the number of conflicts as well as iterated local search algorithms that use an unbounded color palette and aim to use the smallest colors and - as a consequence - the smallest number of colors. We identify classes of bipartite graphs where reoptimization is as hard as or even harder than optimization from scratch, i. e. starting with a random initialization. Even adding a single edge can lead to hard symmetry problems. However, graph classes that are hard for one algorithm turn out to be easy for others. In most cases our bounds show that reoptimization is faster than optimizing from scratch. Furthermore, we show how to speed up computations by using problem specific operators concentrating on parts of the graph where changes have occurred.
Keywords: dynamic optimization; evolutionary algorithms; running time analysis; theory

On the Benefits of Biased Edge-Exchange Mutation for the Multi-Criteria Spanning Tree Problem - Bossek, Jakob; Grimme, Christian; Neumann, Frank (Proceedings of the Genetic and Evolutionary Computation Conference)
Research has shown that for many single-objective graph problems where optimum solutions are composed of low weight sub-graphs, such as the minimum spanning tree problem (MST), mutation operators favoring low weight edges show superior performance. Intuitively, similar observations should hold for multi-criteria variants of such problems. In this work, we focus on the multi-criteria MST problem. A thorough experimental study is conducted where we estimate the probability of edges being part of non-dominated spanning trees as a function of the edges’ non-domination level or domination count, respectively. Building on gained insights, we propose several biased one-edge-exchange mutation operators that differ in the used edge-selection probability distribution (biased towards edges of low rank). Our empirical analysis shows that among different graph types (dense and sparse) and edge weight types (both uniformly random and combinations of Euclidean and uniformly random) biased edge-selection strategies perform superior in contrast to the baseline uniform edge-selection. Our findings are in particular strong for dense graphs.
Keywords: biased mutation; combinatorial optimization; minimum spanning tree; multi-objective optimization

Solving Scalarized Subproblems within Evolutionary Algorithms for Multi-criteria Shortest Path Problems - Bossek, Jakob; Grimme, Christian (Learning and Intelligent Optimization)
The $$\ mathcal NP$$-hard multi-criteria shortest path problem (mcSPP) is of utmost practical relevance, e.~g., in navigation system design and logistics. We address the problem of approximating the Pareto-front of the mcSPP with sum objectives. We do so by proposing a new mutation operator for multi-objective evolutionary algorithms that solves single-objective versions of the shortest path problem on subgraphs. A rigorous empirical benchmark on a diverse set of problem instances shows the effectiveness of the approach in comparison to a well-known mutation operator in terms of convergence speed and approximation quality. In addition, we glance at the neighbourhood structure and similarity of obtained Pareto-optimal solutions and derive promising directions for future work.

Time Complexity Analysis of RLS and (1 + 1) EA for the Edge Coloring Problem - Bossek, Jakob; Sudholt, Dirk (Proceedings of the 15th ACM/SIGEVO Conference on Foundations of Genetic Algorithms)
The edge coloring problem asks for an assignment of colors to edges of a graph such that no two incident edges share the same color and the number of colors is minimized. It is known that all graphs with maximum degree {$Δ$} can be colored with {$Δ$} or {$Δ$} + 1 colors, but it is NP-hard to determine whether {$Δ$} colors are sufficient. We present the first runtime analysis of evolutionary algorithms (EAs) for the edge coloring problem. Simple EAs such as RLS and (1+1) EA efficiently find (2{$Δ$} - 1)-colorings on arbitrary graphs and optimal colorings for even and odd cycles, paths, star graphs and arbitrary trees. A partial analysis for toroids also suggests efficient runtimes in bipartite graphs with many cycles. Experiments support these findings and investigate additional graph classes such as hypercubes, complete graphs and complete bipartite graphs. Theoretical and experimental results suggest that simple EAs find optimal colorings for all these graph classes in expected time O({$Δ\mathscrl$}2m log m), where m is the number of edges and {$\mathscrl$} is the length of the longest simple path in the graph.
Keywords: edge coloring problem; runtime analysis

Multi-Objective Performance Measurement: Alternatives to PAR10 and Expected Running Time - Bossek, Jakob; Trautmann, Heike (Learning and Intelligent Optimization)
A multiobjective perspective onto common performance measures such as the PAR10 score or the expected runtime of single-objective stochastic solvers is presented by directly investigating the tradeoff between the fraction of failed runs and the average runtime. Multi-objective indicators operating in the bi-objective space allow for an overall performance comparison on a set of instances paving the way for instance-based automated algorithm selection techniques.
Keywords: Algorithm selection; Performance measurement

OpenML: An R Package to Connect to the Machine Learning Platform OpenML - Casalicchio, Giuseppe; Bossek, Jakob; Lang, Michel; Kirchhoff, Dominik; Kerschke, Pascal; Hofner, Benjamin; Seibold, Heidi; Vanschoren, Joaquin; Bischl, Bernd (Computational Statistics)
OpenML is an online machine learning platform where researchers can easily share data, machine learning tasks and experiments as well as organize them online to work and collaborate more efficiently. In this paper, we present an R package to interface with the OpenML platform and illustrate its usage in combination with the machine learning R package mlr (Bischl et al. J Mach Learn Res 17(170):1—5, 2016). We show how the OpenML package allows R users to easily search, download and upload data sets and machine learning tasks. Furthermore, we also show how to upload results of experiments, share them with others and download results from other users. Beyond ensuring reproducibility of results, the OpenML platform automates much of the drudge work, speeds up research, facilitates collaboration and increases the users’ visibility online.
Keywords: Databases; Machine learning; R; Reproducible research

Stereoselective Alkyne Hydrogenation by using a Simple Iron Catalyst - Gregori, Bernhard J.; Schwarzhuber, Felix; Pöllath, Simon; Zweck, Josef; Fritsch, Lorena; Schoch, Roland; Bauer, Matthias; Jacobi von Wangelin, Axel (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Navid Kermani - Schulte Eickholt, Swen; Hofmann, Michael; von Stosch, Klaus

Einleitung - Elit, Stefan; Eke, Norbert Otto (Literarische Institutionen)

Narrating Selves from the Bible to Social Media: Introduction to the Forum - Hyvärinen, Matti; Hatavara, Mari; Mildorf, Jarmila (Partial Answers)

Die Antwerpener Börse - Aufstieg, Niedergang und Wandel (VIDEO) - Huybrechts, Yves

Ironische Wendigkeit und poetische Notwendigkeit. Zum Begriff des ,Scheiterns‘ bei Hans Magnus Enzensberger - Diedrich, Alena (Verhinderte Meisterwerke. Gescheiterte Projekte in Literatur und Film)

Tätigkeitsbericht 2007-2017 der Stabsstelle Bildungsinnovationen und Hochschuldidaktik der Universität Paderborn - Neiske, Iris; Vöing, Nera (Personal- und Organisationsentwicklung Forum für Führung, Moderation, Training, Programm-Organisation in Einrichtungen der Lehre und Forschung)

Kurz berichtet. Das E-Tutoren-Programm an der UPB. - Neiske, Iris (Paderborner Universitätszeitschrift (puz))

Jesus-Transformationen. Zum 60. Geburtstag von Martin Leutzsch

Jesus als Metapher. Bildhafte Jesus-Transformationen im NT und darüber hinaus - Niepert-Rumel, Sophia Stephanie Gundula (Jesus-Transformationen)

How ideas come into being: Tracing intertextual moments in grades of objectification and publicness - Karsten, Andrea; Bertau, Marie-Cécile (Frontiers in Psychology)
How do ideas come into being? Our contribution takes its starting point in an observation we made in empirical data from a prior study. The data center around an instant of an academic writer’s thinking during the revision of a scientific paper. Through a detailed discourse-oriented micro-analysis, we zoom in on the writer’s thinking activity and uncover the genesis of a complex idea through a sequence of interrelated moments. These moments feature different degrees of “crystallization” of the idea; from gestures, a sketch, a short written note, oral explanations to a final spelled-out written argument. For this contribution, we re-analyze the material, asking how the idea gets formed during the thinking process and how it reaches a tangible form, which is understandable both for the thinker and for other persons. We root our analysis in a notion of language as social, embodied, and dialogical activity, drawing on concepts from Humboldt, Jakubinskij, and Vygotsky. We focus our analysis on three conceptual nodes. The first node is the ebbing and advancing of language in idea formation – observable as a trajectory through linguistically more condensed or more expanded utterance forms. The second node is the degree of objectification that the idea reaches when it is performed differently in a variety of addressivity constellations, i.e., whether and how it becomes understandable to the thinker and to others in the social sphere. Finally, the third node is the saturation of the idea through what we call intrapersonal intertextuality, i.e., its complex and dialogically related re-articulations in a sequence of formative moments. With these considerations, we articulate a clear consequence for theorizing thinking. We hold that thinking is social, embodied, and dialogically organized because it is entangled with language. Ideas come into being and become understandable and communicable to other persons only by and within their different, yet, intertextually related formations.
Keywords: idea formation; language activity; objectification; intrapersonal intertextuality; articulation; Jakubinskij; Vygotsky; Humboldt

Fukś, Henryk, “Magic Squares of Subtraction of Adam Adamandy Kochański”, in: M. Zack/D. Schlimm (Hgg.), Research in History and Philosophy of Mathematics, Birkhäuser/Springer: Cham 2017 (Proceedings of the Canadian Society for History and Philosophy of Mathematics), 81–95 - Peckhaus, Volker (Mathematical Reviews MR3823511)

Farbe im Prozess optischer und haptischer Wahrnehmung – ein Beispiel aus dem Kunstunterricht - Pauls, Karina (Impulse.Kunstdidaktik)

Rezension zu Kunibert Bering – Rolf Niehoff: Horizonte der Bild-/Kunstgeschichte mit kunstpädagogischem Blick – Band 2 - Pauls, Karina (BDK Mitteilungen 2/2019)

Die Entwicklung der Sterne. Eine elementarisierte Betrachtung. Dissertation. Universi-Verlag, Siegen, ISBN 978-3-96182-050-4 - Hohmann, Sascha
In der vorliegenden Arbeit werden Wege untersucht, um die stellare Physik zu elementarisieren und in Lehrkonzepte zu überführen. Damit sollen angehenden oder tätigen Lehrenden der Physik Mittel an die Hand gegeben werden, die ein angemessenes Theorieverständnis ermöglichen. In erster Linie wird damit bezweckt, eine wesentliche Forschungsmethode der Astrophysik - nämlich Himmelskörper mathematisch so zu modellieren, dass an ihrer Oberfläche beobachtbare Phänomene vorhergesagt werden - im Lehr- und Unterrichtsbetrieb zu präsentieren. Bekanntlich werden viele astrophysikalische Phänomene in der Lehrliteratur nur phänomenologisch abgehandelt, wodurch das Desiderat entsteht, dass die eigentliche Untersuchungsmethodologie nur ungenügend vermittelt wird. In der Promotionsschrift wird berücksichtigt, dass Astrophysik nur einen kleinen Teil eines Physikstudiums für das Lehramt ausmacht, der Stoff daher komprimiert und ohne tiefere Vorkenntnisse zu behandeln ist. Weiterhin wird anhand der Analyse von Aufgaben zweier Schulbuchreihen gezeigt, dass quantitatives Arbeiten insbesondere in der Sekundarstufe II einen großen Teil des Physikunterrichts ausmacht und sich daher mathematisches Modellieren für Übungen anbietet. Von jeher unterliegt die Astrophysik einem besonders kritischen, erkenntnistheoretischen Blick, da sie naturgegeben weitgehend auf die experimentelle Untersuchung ihrer Forschungsgegenstände verzichten muss und nur anhand passiver Beobachtungen zu Erkenntnissen gelangen kann. Eine sinnvolle Beschäftigung mit modernen Forschungsresultaten der Astrophysik ist daher ohne eine besondere Einbindung in einen erkenntnistheoretischen Rahmen kaum vorstellbar. Daher werden in der vorliegenden Schrift erkenntnistheoretische Grundlagen vorgestellt, die einen kritischen Blick auf die Entwicklung einer astrophysikalischen Theorie ermöglichen. Es werden Varianten aufgezeigt, die Sterne sowohl als quasi-statische Objekte zu betrachten als auch ihre Entwicklung näher zu beleuchten. Speziell auf die Bedingungen zur Entwicklung von Leben auf einem Planeten und die dabei bestehenden Zusammenhänge zum Zentralgestirn wird eingegangen, da die Frage nach Leben auf anderen Planeten ein für Lernende interessantes Thema ist. Die präsentierten Modelle benötigen dabei nur Mathematik und Physik der Grundvorlesungen, teilweise genügt Abiturniveau.

Wie groß ist ein Neutronenstern? Elementarisierende Überlegungen und Abschätzungen - Hohmann, Sascha (PhyDid B)

Stellare Voraussetzungen für die Entstehung von Leben - Hohmann, Sascha (Astronomie + Raumfahrt im Unterricht)

Heisenberg und seine Suche nach der "Weltformel" - Hohmann, Sascha (Astronomie + Raumfahrt im Unterricht)

Migration in finsteren Zeiten. Über die Notwendigkeit der Erschaffung öffentlicher Räume - Robaszkiewicz, Maria Anna (Schriften der Arbeitsstelle Menschenrechte der Otto-von-Guericke-Universität Magdeburg)

Process Parameter Optimization to Improve the Mechanical Properties of Arburg Plastic Freeformed Components - Moritzer, Elmar; Hirsch, André; Hecker, Felix (30th Annual International Solid Freeform Fabrication Symposium)
The Arburg Plastic Freeforming (APF) is an additive manufacturing process that allows three-dimensional, thermoplastic components to be produced in layer by layer. The components are generated by depositing fine, molten plastic droplets. One of the main advantages of the APF process is the open machine control. Thus, the process parameters can be adapted and optimized for the individual applications. The optimization is carried out on the basis of a variation of the process parameters using a statistical design of experiments. Relevant process parameters are the layer thickness, the form factor, the raster and delta angle as well as the overlap between the contour and the filling of a layer. In addition, the nozzle and build chamber temperatures are varied. Using this procedure, the effects of the influencing parameters on the mechanical properties and the interactions between the influencing parameters are analyzed and converted into mathematical models. On the basis of the results and the models, guidelines will be developed to assist the user of APF technology in the systematic process configuration for their own applications. The material used is ABS, one of the most frequently used amorphous thermoplastics in additive manufacturing. The mechanical properties are determined on the basis of tensile tests and the characteristic values tensile strength, elongation at break and Young's modulus. The results should show the performance of the APF technology in regard to the mechanical properties.

Gift Purchases as Catalysts for Strengthening Customer–Brand Relationships - Eggert, A.; Steinhoff, Lena; Witte, C. (Journal of Marketing)

Relationship Marketing in the Digital Age - Palmatier, R. W.; Steinhoff, Lena

Online Relationship Marketing - Steinhoff, Lena; Arli, D.; Weaven, S.; Kozlenkova, I. V. (Journal of the Academy of Marketing Science)

Enhancing Loyalty Program Effectiveness by Stimulating Member Activity along the Customer Journey - Steinhoff, Lena; Zondag, M. (Proceedings of the 48th European Marketing Academy (EMAC) Conference, Hamburg)

Inklusion aus der Sicht von Kindern mit dem Förderschwerpunkt Lernen – Überprüfung von Messinvarianz in verschiedenen schulischen Kontexten. - Knickenberg, Margarita; Zurbriggen, Carmen; Schwab, Susanne; Gebhardt, Markus

Students with emotional or behavioral problems: Their emotional experience in the classroom during peer interactions. - Knickenberg, Margarita; Zurbriggen, Carmen; Venetz, Martin

Individual and institutional determinants for primary school teachers’ self-efficacy beliefs regarding inclusive education – Results from qualitative interviews. - Knickenberg, Margarita; Frank, Hellmich; Marwin Felix, Löper

Potential influencing factors for teachers’ self-efficacy beliefs concerning inclusive education - Knickenberg, Margarita; Marwin Felix, Löper; Frank, Hellmich

Assessing social interaction quality with the Experience Sampling Method - Knickenberg, Margarita; Zurbriggen, Carmen; Venetz, Martin

Peer interactions in everyday school life versus leisure time of adolescents and their emotional experience. - Knickenberg, Margarita; Zurbriggen, Carmen; Hinni, Chantal; Venetz, Martin

Erfassung von Merkmalen inklusiven Unterrichts mit der Experience Sampling Method. - Knickenberg, Margarita; Zurbriggen, Carmen

Applicability of ESM in School: Quality of students' social interaction - Knickenberg, Margarita; Chantal, Hinni

Das gesungene Lied im Religionsunterricht - zwischen Ritualisierung und Instrumentalisierung - Hoyer, Isabelle; Kohlmeyer, Theresa (Praxis des RU)